A Comparative Study Between the Conventional Method and the Use of Powdered Activated Carbon in Iron Reduction from Groundwater - Andrew Mbabaali (Uganda Christian University, 2024)
This report was specifically looking at the comparison between the conventional treatment method (aeration followed by settling and filtration) and the use of Powdered Activated Carbon (PAC) in an adsorbent filter in total iron reduction from groundwater sources. The PAC was prepared from sawdust. The water sample was collected from iron contaminated ground water source (borehole with hand pump). Both treatment methods indicated above (conventional and adsorption) were applied to check the total iron reduction from the ground water source and the results were compared in order to determine which method could be more effective in total iron reduction. Total iron levels were tested both before and after the treatment and the results showed that the conventional method was able to reduce the total iron concentration by 95.22% (from 41.44mg/L to 1.98mg/L) while on the other hand, PAC layer thicknesses of 2.5cm, 5cm, and 7.5cm were able to reduce the total iron concentration by 99.08%, 99.20%, and 99.40% respectively between 41.44mg/L and 0.38mg/L, 41.44mg/L and 0.33mg/L and 41.44mg/L and 0.25mg/L respectively . However, the reduced iron levels to (1.98mg/L and 0.33mg/L for conventional and PAC respectively) were still above the permissible limits compared to the Uganda National Standards for treated potable water which is 0.3mg/L. But since 0.33mg/L total iron is also within the permissible limit of the Uganda National Standards for untreated potable water (1mg/L), it was considered to be safe at household level.